Antiviral Activity of Panavir in Experimental Infection Due to Morbillivirus in Cell Cultures - S. G. Markushin; A. A. Litvin (Антибиотики и Химиотерапия)
Antiviral activity of Panavir was studied in a model of experimental infection due to Morbillivirus in subcultures of cells Vero and B-16. It was shown that at multiplicity of the infection (0.001-0.0001 TCD50/cell) Panavir inhibited reproduction of the virus in concentrations of 12-100 мcg/0.2 ml.